The Effect of Taxes and Bonus Mechanisms in Moderating Profitability on Transfer Pricing - Mamay Komarudin; Naufal Affandi; Ende Ende; Nugrahini Kusumawati; Siti Fatonah; Surti Zahra (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2023)
One factor that encourages companies to do transfer pricing is the bonus mechanism. Bonusecanism is used as a moderating, reinforcing, or motivation-weakening variable of tranfer pricing. The purpose of this study is to analyze the causality between tax and transfer pricing in companies related to the manufacturing and non-financial services sectors in Indonesia and to analyze the role of bonus mechanism moderators in strengthening the effect of profitability on transfer pricing in companies related to the manufacturing and non-financial services sectors in Indonesia. This type of research is explanatory research, which explains one variable's causality relationship to another. This study used the analysis of the Granger causality test and hypothesis testing using the coefficient of determination test, F test and t-test. The sample in this study is companies members of the KOMPAS 100 index in 2010-2020, totaling 100 companies. Based on the study's results, it can be concluded that: 1) There is a causality relationship between tax and transfer pricing. The amount of tax has a positive effect on transfer pricing. On the other hand, transfer pricing also positively affects the amount of tax. This suggests a causality link between tax and transfer pricing and as a form of tax avoidance by multinational companies; 2) The role of the bonus mechanism does not moderate the amount of profitability to transfer pricing. The decision of managers to pursue bonuses does not affect the amount of profitability to transfer pricing.